CYBER-FREEDOM’S DILEMMA: COUNTRY’S POINT OF VIEW - Khanisa Khanisa (Widyariset, 2013)
The usage of cyber world in any kind of field is growing larger as the expand of technology. There are inevitable shift to cyber world due to its ability to make a more effective communication, cross the geographical border, and create the feeling of freedom to do anything. Although, this phenomenon also brings questions in how far freedom can be exercised and can a country control the freedom of the cyber world. With descriptive method using secondary data, this paper will try to explain the dilemma and answer those questions using a country point of view. This study aiming to get an understanding about cyber freedom, the implication in international politics, and the acceptable country’s role in it.